Three Phase Induction Motor Rotation Direction Control Using PLC Omron CP1E and HMI NB7W-TW00B - I Made Ari Nrartha; Muhamad Nudisantana Riswandi; Supriono Supriono (Journal of Renewable Energy, Electrical, and Computer Engineering, 2022)
Rotation direction control on three-phase electric motors is very much needed in industry as driving machines such as mixers, grinders, conveyors, and transportation machines. This study proposes controlling the rotational direction of a three-phase induction motor automatically using an Programmable Logic Control (PLC) Omron CP1E which is connected to the Human Machine Interface (HMI) NB7W-TW00B. The HMI NB7W-TW00B provides timing instructions to the PLC to change the direction of rotation of the induction motor. To provide safe operation of the induction motor due to changes in the direction of rotation, the PLC control was given a delay of 1 to 4 seconds. The results show that a delay of 1 to 4 seconds provides a linear reduction in speed before the motor rotates in the opposite direction.